Writings on psychoanalysis : Freud and Lacan - Althusser, Louis, 1918-1990 (European perspectives., 1996)
A prominent member of the French structuralist movement, Louis Althusser was influential for reinvigorating Marxist thought in France in the 196Os with celebrated works such as For Marx and Reading Capital. Yet many readers are not as familiar with the profound impact of psychoanalysis on Althusser's life and work. Writings on Psychoanalysis gathers, for the first time, Althusser's major essays on psychoanalytic thought. The volume begins with Freud and Lacan, which lays the groundwork for comprehending Althusser's entry into psychoanalysis. Letters to D. was the result of Althusser's fervent reading of Rene Diatkine's paper "Aggressiveness and Fantasies of Aggression," years before Diatkine was his psychoanalyst. Invited by Leon Chertok to participate in the "International Symposium on the Unconscious," at the Tbilisi colloquium, the chapter The Tbilisi Affair presents Althusser's essay "The Discovery of Dr. Freud." The chapter In the Name of the Analysands ... reprints Althusser's "Open Letter to Analysands and Analysts in Solidarity with Jacques Lacan," written the day after the famous meeting on the dissolution of the Ecole Freudienne de Paris. Characterizing Lacan as a "magnificent and pitiful Harlequin," the 'open letter' relates Althusser's untimely outburst at that assembly and the "spectacular and violent intervention he subsequently made in the presence of Lacan." The volume closes with the correspondence between Althusser and Lacan, detailing their first and last meetings with each other and the launching of one of the central alliances of contemporary French thought.